Didactic Engineering and Learning Objects: A Proposal for Teaching Parabolas in Analytical Geometry - de Sousa, Renata Teófilo; Alves, Francisco Régis Vieira (Indonesian Journal of Science and Mathematics Education, 2022)
This work aims to investigate the feasibility of using a Learning Object built in GeoGebra software and its potential for teaching parabolas in Analytical Geometry, having as support for its replication in a teaching session the Theory of Didactic Situations. The methodology adopted was Didactic Engineering, in its first two phases – preliminary analysis and a priori analysis. In the preliminary analysis, some epistemological and didactic aspects that permeate the teaching of parabolas, the concept of Learning Objects and the Theory of Didactic Situations were raised. In the a priori analysis, we present the Learning Object called Suspension Bridge and its manipulation in GeoGebra for the exploration of the parabola, as well as a student's attitudinal prediction. Thus, we seek to collaborate with the development of new approaches to teaching this topic, contributing to the advancement of the use of educational technologies integrated into the teaching of mathematics.